ЧЎЛЯЛПИЗ (Ziziphora tenuior) ЎСИМЛИГИНИНГ ПОЯ ВА БАРГ ЭКСТРАКТЛАРИНИ ЭРИТРОЦИТЛАР МЕМБРАНАСИГА ТАЪСИРИ - Мансуров М.М, Файзиев Д.Д, Хамидова О.Ж, Қурбанназарова Р.Ш, Мерзляк П.Г, Сабиров Р.З (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article presents the results of the effect of the stem and leaf extract of Cholyapiz plant on erythrocyte membranes. It was found that the extract has a low cytotoxic effect on erythrocyte cells.